Chemical Source Localization using Mobile Robots in Indoor Arena - Yuli Zhang; Xiaoping Ma; Yanzi Miao (Institute of Advanced Engineering and Science, 2013)
This paper presents a virtual-physics force based control strategy for swarm robotic chemical source localization. The control force includes: structure formation force, goal force, and obstacle avoidant force. For swarm formation, the robots maintain the regular polygon formation and a virtual robot is located at the center of the polygon. The motion of the virtual robot depends on the goal force which obtained from the sensor observations of the robots. Once the virtual robot moved to a new place, the robots would also move as a single body with the structure formation force and obstacle avoidant force. In this paper, we adopted chemotaxis as plume tracing algorithms. Simulation experiments in indoor arena without obstacle and with obstacles using different robot number are carried out respectively, and the results show that the proposed strategy can effectively navigate the mobile robotics swarms to the chemical source once selecting proper number of robots. DOI: http://dx.doi.org/10.11591/telkomnika.v11i7.2819